Validation of the revised injury severity classification score in patients with moderate-to-severe traumatic brain injury. Issue 1 (January 2015) - Raj, Rahul; Brinck, Tuomas; Skrifvars, Markus B.; Kivisaari, Riku; Siironen, Jari; Lefering, Rolf; Handolin, Lauri
Abstract: Introduction: By analysing risk-adjusted mortality ratios, weaknesses in the process of care might be identified. Traumatic brain injury (TBI) is the main cause of death in trauma, and thus it is crucial that trauma prediction models are valid for TBI patients. Accordingly, we assessed the validity of the RISC score in TBI patients by internal and external validation analyses. Methods: Patients with moderate-to-severe TBI admitted to the TraumaRegister DGU ® (TR-DGU) and the trauma registry of Helsinki University Hospital (TR-THEL) in 2006–2011 were included in this retrospective open cohort study. Definition of moderate-to-severe TBI was head abbreviated injury scale of 3 or higher. Subgroup analysis for patients with isolated and polytrauma TBI was performed. The performance of the RISC score was evaluated by assessing its discrimination (area under the curve, AUC) and calibration (Hosmer–Lemeshow [H–L] test). Results: Among the 9106 and 809 patients with moderate-to-severe TBI admitted to TR-DGU and TR-THEL, unadjusted mortality was 26% and 23%, respectively. Internal and external validation of the RISC score showed good discrimination (TR-DGU AUC 0.89, 95% confidence interval [CI] 0.88–0.90 and TR-THEL AUC 0.84, 95% CI 0.81–0.87), but poor calibration ( p  < 0.001) in patients with moderate-to-severe TBI. Subgroup analysis found the discrimination only to be modest in isolated TBI (AUC 0.76) and calibration to be particularly poor in polytrauma TBI (TR-DGU H–L = 4356, p  < 0.001; TR-THEL H–L 112, p  < 0.001). Conclusion: The RISC score was found to be of limited predictive value in patients with moderate-to-severe TBI. A new general trauma scoring system that includes TBI specific prognostic factors is warranted.